'A kind of ritual Pakeha tikanga'-- Maori experiences of hospitalisation : a case study : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Nursing at Massey University (Albany), New Zealand - Barton, Pipi (Massey University, 2008)
Minimal literature exists relating to the experiences of Maori within the New Zealand public hospital system. Maori are highly represented in morbidity and mortality statistics and are high users of the secondary health care system. A Case Study methodology with a Maori centred approach was used to describe Maori experiences of hospitalisation. Multiple sources of evidence were gathered, including participant interviews, statistical data from the New Zealand Health Information Service, and international literature relating to indigenous experiences of hospitalisation. Eleven people (nine female and two males) identifying as Maori, of various iwi (tribal) affiliations and from a range of regions, participated in the interviews. All participants had either been admitted, or cared for by a family member who had been admitted to a medical or surgical ward in a public hospital anywhere in New Zealand within the last 15 years. Participants were aged between 20 to 75 years. All interviews were audio recorded, transcribed and then thematically analysed. A retrospective interrupted time series design was used to examine length of stay for Maori patients receiving treatment in the secondary medical and surgical setting, from 1989-2004. The data included the records of all medical and surgical discharges for Maori and non-Maori from the New Zealand public hospitals. Medical and surgical admissions were screened to include those over the age of 17 years and who had a length of stay greater than 1 day and less than 90 days. From the analysis of all the data three key interpretations emerged: 1. Maori are marginalised within the mainstream health system. 2. Maori believe that the hospital environment is not conducive to healing. 3. Maori experiences in hospital contribute to their decision to leave as soon as possible. The recommendations include the integration of more culturally acceptable and appropriate interventions within secondary and tertiary health services, and a review of the effectiveness of cultural safety education in practice and inclusion/revision of the cultural competence for all health care workers.
Keywords: Maori health; Hospitalisation; Cultural safety; Nursing; Fields of Research::320000 Medical and Health Sciences::321100 Nursing